High carbon dioxide, modified-atmosphere packaging (MAP) for beef steaks - Luchsinger, S.E.; Hunt, Melvin C.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To determine the effects of storage in a high-carbon dioxide, modified-atmosphere package (MAP) on shelf life, beef strip steaks were packaged under 30% CO2-70% N2 and stored for up to 42 days at 30 or 38 ̊F. Aerobic plate counts (APC) and lactic acid bacteria (LAB) counts in these ExtendPak™ packages were well below the threshold of spoilage even after 42 days of MAP storage. After 28 days of storage, steaks stored in vacuum packages had APC counts 1.0 log 10 greater than steaks in MAP. APCs increased during a 5-day display period in steaks store d in vacuum packages, but no increases occurred with MAP. Repackaged steaks from vacuum packages bloomed to a brighter red color than steaks stored in MAP, but MAP steaks were more color stable through display. Microbial data indicate d that steaks can be stored for up to 42 days using this promising MAP system. The long storage life of MAP steaks allows packers and retailers more flexibility to respond to variable consumer demand, without the threat of product spoilage.
Keywords: Beef; Packaging; Beef steaks; Shelf life